2023
DOI: 10.1371/journal.pgph.0001473
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a combined TB/HIV intervention on the incidence of TB infection among adolescents and young adults in the HPTN 071 (PopART) trial communities in Zambia and South Africa

Abstract: Background HPTN071 (PopART) was a cluster randomized trial conducted in Zambian and South African (SA) communities, between 2013–2018. The PopART intervention (universal HIV-testing and treatment (UTT) combined with population-level TB symptom screening) was implemented in 14 communities. The TREATS study (2017–2021) was conducted to evaluate the impact of the PopART intervention on TB outcomes. We report on the impact of the combined TB/HIV intervention on the incidence of TB infection in a cohort of adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interferon-γ release blood tests (IGRAs) and tuberculin skin tests (TST) are commonly used to diagnose Mtb infection, but school-based surveys are rare. A recent study reported a TB infection incidence rate of 17.1 per 100 person-years among adolescents and young adults in South African communities of a cluster randomized trial [ 63 ]. The prevalence of TB infection among 12 to 18-year-olds is approximately 50% [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-γ release blood tests (IGRAs) and tuberculin skin tests (TST) are commonly used to diagnose Mtb infection, but school-based surveys are rare. A recent study reported a TB infection incidence rate of 17.1 per 100 person-years among adolescents and young adults in South African communities of a cluster randomized trial [ 63 ]. The prevalence of TB infection among 12 to 18-year-olds is approximately 50% [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…AYP were invited from the community to a health facility (Zambia) or a clinical research site (South Africa) where they were enrolled. Details of the cohort enrollment have been published elsewhere [ 19 ]. The study recruitment period lasted from July 12, 2018 to May 24, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…AYP were invited from the community to a health facility (Zambia) or a clinical research site (South Africa) where they were enrolled. Details of the cohort enrollment have been published elsewhere [19]. The study recruitment period lasted from July 12, 2018 to May 24, 2019. Study participants aged � 18 years signed an informed consent form prior to enrolment, whilst for participants � 17 years both assent and parental consent were obtained.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation